PERFORMANCE OVERVIEW OF THE WASTEWATER TREATMENT PLANT (WWTP) AT PERUMDA TIRTANADI CEMARA, PERCUT SEI TUAN DISTRICT, MEDAN - Ridho Afdal Marunduri; Khalisa Aisyah Signora; Ipak Sinantin; Kurnia Permata Sari; Niken Natani Sabilla; Syafran Arazzy (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Population growth and increased domestic activities in urban areas have led to an increase in the volume of wastewater produced annually. If domestic wastewater is not treated properly, it can cause environmental pollution such as decreased water and soil quality, the emergence of unpleasant odors, and the risk of spreading disease. To overcome these problems, an effective wastewater treatment system is needed through a Wastewater Treatment Plant (WWTP). Objective: This study aims to determine the process and stages of domestic wastewater treatment and assess the effectiveness of the performance of the Perumda Tirtanadi Cemara Branch WWTP in reducing the levels of major pollutants such as BOD, COD, TSS, oil and fat, and ammonia to comply with domestic wastewater quality standards based on the Minister of Environment and Forestry Regulation No. 68 of 2016, Method: The research method used is descriptive qualitative, with data collection techniques through interviews, direct observation, and laboratory document reviews of the results of wastewater quality testing at the inlet and outlet of the WWTP, Results: The results of the study showed that the wastewater treatment process at the PDAM Tirtanadi Cemara Branch WWTP was carried out through several stages, namely coarse screening, fine screening, grit chamber, anaerobic reactor (UASB), aeration pond, facultative pond, and sludge drying bed. Based on the analysis results, there was a significant decrease in pollutant levels: BOD from 30.20 mg/L to 7.85 mg/L (74% efficiency), COD from 50 mg/L to 13 mg/L (74% efficiency), TSS from 42 mg/L to 11 mg/L (73.80% efficiency), oil and fat from 0.07 mg/L to 0.02 mg/L (71.24% efficiency), and ammonia from 7.5 mg/L to 5.6 mg/L (25.33% efficiency). The pH remained stable at 7.19, within the quality standard range of 6–9. Therefore, it can be concluded that the wastewater treatment plant (WWTP) of the Tirtanadi Water Company (PDAM) in the Cemara Branch performs well and is effective in reducing domestic wastewater pollutant levels. Therefore, the treated water meets quality standards and is safe for discharge into aquatic environments.